х³ - x² = 0
х²(х - 1) = 0
х² = 0 или х - 1 = 0
х = 0 или х = 1
x³ - x = 0
х(х² - 1) = 0
х(х - 1)(х + 1) = 0
х = 0 или х - 1 = 0 или х + 1 = 0
х = 1 или х = -1
4y - y³ = 0
y(4 - y²) = 0
y(2 - y)(2 + y) = 0
y = 0 или 2 - y = 0 или 2 + y = 0
y = 2 или y = - 2
5z³ - 5z = 0
5z(z² - 1) = 0
5z(z - 1)(z + 1) = 0
5z = 0 или z - 1 = 0 или z + 1 = 0
z = 0 или z = 1 или z = - 1
z - 9z³ = 0
z(1 - 9z²) = 0
z(1 - 3z)(1 + 3z) = 0
z = 0 или 1 - 3z = 0 или 1 + 3z = 0
z = 1/3 или z = -1/3
х³ - x² = 0
х²(х - 1) = 0
х² = 0 или х - 1 = 0
х = 0 или х = 1
x³ - x = 0
х(х² - 1) = 0
х(х - 1)(х + 1) = 0
х = 0 или х - 1 = 0 или х + 1 = 0
х = 1 или х = -1
4y - y³ = 0
y(4 - y²) = 0
y(2 - y)(2 + y) = 0
y = 0 или 2 - y = 0 или 2 + y = 0
y = 2 или y = - 2
5z³ - 5z = 0
5z(z² - 1) = 0
5z(z - 1)(z + 1) = 0
5z = 0 или z - 1 = 0 или z + 1 = 0
z = 0 или z = 1 или z = - 1
z - 9z³ = 0
z(1 - 9z²) = 0
z(1 - 3z)(1 + 3z) = 0
z = 0 или 1 - 3z = 0 или 1 + 3z = 0
z = 1/3 или z = -1/3